Transfer pricing or formula apportionment? Tax-induced distortions of multinationals' investment and production decisions - Jan Thomas Martini; Rainer Niemann; Dirk Simons (Arbeitskreis Quantitative Steuerlehre (arqus), 2007)
Multinational groups (MNGs) produce a major part of global output. Further, a substantial fraction of international transactions happens to be internal, i.e., intermediate products and services are traded between group members. Thus, the problem of co-ordinating economic decisions like investment or production within such large entities has been widely recog-nized in the theoretical and empirical literature. The findings suggest that transfer prices are a widespread device for splitting up complex decision situations and allocating the responsibility for the resulting subproblems to several decision makers. Apart from its co-ordination function transfer pricing is also used for tax purposes. Legally independent group members realize intra-group sales and contribute to a single product. Taxable group profits are often allocated among the participating companies by means of transfer prices. In this case, from the group's perspective, transfer pricing is a device of international tax planning. Of course, national tax authorities have been aware of potential misuse. In Europe, the problem has become especially severe since the mid-European countries joined the EU. Due to the emerging large tax rate differentials, tax revenues of high-tax legislations eroded. For mitigating this problem formula apportionment (FA) is discussed intensively. Under FA, a common tax base is calculated and divided among the host countries in accordance with given apportionment factors. As a consequence, earnings management fails to re-allocate profits to low-tax legislations and tax base erosion seems to be stopped. However, FA could even be more harmful than transfer pricing because under FA income shifting would require changing economic decisions instead of just taking advantage of accounting options. In addition to the erosion of tax revenues, capital investments and employment could decrease in high-tax legislations. The goal of our paper is to analyze the impact of different international tax allocation regimes on the MNG's investment and production decisions. In our theoretical model, we derive optimal decisions under transfer pricing and FA. A prominent result of our analysis is that FA offsets the advantages of decision decentralization as it reverses the separation of responsibility areas. It is not clear whether FA is desirable from a fiscal or an entrepreneurial perspective. We show that the effects of FA compared to transfer pricing depend strongly on the parameter setting under consideration. One of the most important determinants is the internal decision procedure within the MNG.
Keywords: H25; G21; M41; 330; Capital budgeting; Formula apportionment; International Taxation; Investment Incentives; Multinational Groups; Transfer Pricing; Doppelbesteuerung; Transferpreis; Formula Apportionment; Steuerwirkung; Multinationales Unternehmen; Direktinvestition; Besteuerungsgrundsatz; Theorie